Comparative study of the registration procedure of locally manufactured herbal products in selected African countries - Gambo, Aisha; Gqaleni, Nceba; Lebina, Limakatso; Mathibe, Lehlohonolo J. (Frontiers in Pharmacology, 2025)
BackgroundRecognizing the widespread use of herbal medicines, regulating them to ensure their safe registration, quality, and efficacy is of vital importance. Various countries in Africa have developed guidelines for the registration and subsequent market authorization of herbal medicine products. In this article, we aim to examine the registration procedures of locally manufactured herbal medicine (LMHM) products in four selected African countries for comparative purposes.MethodDocument analysis was used to evaluate and interpret official and legal documents identified from the official websites of the drug regulatory authorities (DRAs) in the selected countries [Ghana, Nigeria, Uganda, and Zimbabwe]. These countries are selected based on the study’s objectives to examine the regulatory framework, guidelines, and legislation on the registration procedures and requirements of LMHMs.ResultsIn Ghana, Nigeria, and Uganda, the registration process offers a simplified pathway for LMHMs before market authorization. In Nigeria, LHMHs are listed, whereas in both Ghana and Uganda, they are notified. In Zimbabwe, herbal products are registered as either complementary medicines for general sale or pharmacy complementary medicines. In Nigeria and Uganda, the herbal product will undergo 2 years of pharmacovigilance for post-market surveillance after approval. Products are recalled when complaints occur during pharmacovigilance. In Ghana, yearly and periodic renewals are being done for already registered products. In Uganda, after 2 years of product tracking, the herbal product is then fully registered with the National Drug Authority. The minimum requirements for registering herbal medicines are to ensure product safety, efficacy, and quality. In all selected countries, emphasis is placed on safety and quality. Additionally, experiences reported by physicians, traditional practitioners, or treated patients also serve as evidence for therapeutic efficacy. In all countries, herbal products must conform to existing labeling regulations.ConclusionThe registration of LMHMs is simplified in selected African countries. However, despite this flexibility, few LMHM products get registered and obtain market authorization. Drug regulatory authorities in Africa must address the challenges that hinder the registration of herbal products and take action to promote the local production of herbal medicines while complying with the fundamental registration criteria for product safety, efficiency, and quality control.